Dimensional Ridge Preservation with a Novel Highly Porous TiO 2 Scaffold: An Experimental Study in Minipigs - Tiainen, Hanna; Verket, Anders; Haugen, Håvard J.; Lyngstadaas, S. Petter; Wohlfahrt, Johan Caspar (International Journal of Biomaterials, 2012)
Despite being considered noncritical size defects, extraction sockets often require the use of bone grafts or bone graft substitutes in order to facilitate a stable implant site with an aesthetically pleasing mucosal architecture and prosthetic reconstruction. In the present study, the effect of novel TiO2 scaffolds on dimensional ridge preservation was evaluated following their placement into surgically modified extraction sockets in the premolar region of minipig mandibles. After six weeks of healing, the scaffolds were wellintegrated in the alveolar bone, and the convex shape of the alveolar crest was preserved. The scaffolds were found to partially preserve the dimensions of the native buccal and lingual bone walls adjacent to the defect site. A tendency towards more pronounced vertical ridge resorption, particularly in the buccal bone wall of the nongrafted alveoli, indicates that the TiO2 scaffold may be used for suppressing the loss of bone that normally follows tooth extraction.